Knowledge levels and preference reasons regarding the doping of U23 Turkish National Team athletes: Doping knowledge levels and preference reasons - Yalcin, Ilimdar; Calik, Fehmi; Ece, Cuma; Geri, Serdar; Seker, Ramazan; Yalcin, Seda (Progress in Nutrition, 2019)
The aim of this study was to determine the knowledge level and preference reasons of U23 Turkish National Team athletes about doping. The sample of the study was created by 100 U23 Turkish National Team athletes from different branches. 5-points likert-type scale and a questionnaire consisting of 29 questions was applied to the athletes. In the analysis of the obtained data, descriptive statistics (percentage and frequency) and chi-square test were used. As a result, it was determined that 47% of athletes had enough knowledge about doping, and 81% of them knew that doping had great damages on health, but they were indecisive about the usage of doping. Although athletes tend to use doping, this result may be due to the risk of being caught by the World Anti-Doping Agency.